Cell-cycle regulation of B-Myb protein expression: specific phosphorylation during the S phase of the cell cycle - Robinson, C; Light, Y; Groves, R; Mann, D; Marias, R; Watson, R (Oncogene, 1996)
Previous studies revealed that transcription of B-Myb, which encodes a transcription factor related to the c-Myb proto-oncoprotein, is cell-cycle regulated by an E2F transcription factor-mediated repression mechanism operating in G0/G1. To begin to determine the consequences of transcriptional regulation on B-Myb function, we report here further studies of B-Myb protein expression in the cell cycle. We found that G0-arrest of serum-deprived mouse fibroblasts was achieved without significant reduction in B-Myb levels, moreover, over-expression of B-Myb in stably transfected cells did not prevent their entry into G0. Following serum-induction of arrested fibroblasts, B-Myb abundance increased as cells entered S phase to levels significantly greater than found in cycling cells. This was accompanied by the appearance of a novel phosphorylated form of B-Myb (112 kDa) of distinctly lower electrophoretic mobility than B-Myb present in G1 (110 kDa). The 112 kDa species was S phase-specific even in transfected cells overexpressing B-Myb. Consistent with modification in the S phase of the cell cycle, preliminary evidence suggested that a cyclin A/cdk2, but not cyclin E/cdk2 or cyclin D1/cdk4, complex could induce a similar electrophoretic mobility change in baculovirus-specified B-Myb. These findings show that B-Myb expression may be subject to two levels of control during the cell cycle, transcription and protein phosphorylation.